Tertiary Education is Indispensable to Achieve the Sustainable Development Goals - Salmi, Jamil (International Higher Education, 2020)
For a long time, the crucial contribution of tertiary education to economic and social development has been understated by the international community. But the global commitment to achieving the Sustainable Development Goals (SDGs) has made it harder to ignore that strong and dynamic tertiary education systems are indispensable to make substantial progress on the 17 SDGs.